Changes in the biochemical parameters of cherry berries depending on the variety and method of freezing - Vasylyshyna , O. V.; Postolenko , Ye. P. (Scientific Progress & Innovations, 2019)
The purpose of the article is to study the influence of variety peculiarities and the method of freezing on quality indices of cherry berries. Research methods. The research was carried out during 2016−2018 with berries of cherry varieties: Zhadana, Shans, Elehantna, Optymistka, Podbielska, Alfa, Pamiat Artemenka, grown at the Research Station of Pomology named after L. P. Symyrenka of the IH NAAS. Fruits of berries were picked at the consumer stage of maturation, then they were presorted, inspected, washed, frozen in plastic cups at the temperature of -22−24 °C in prepared sugar syrups according to the following variants: in bulk (control); in 25 % sugar syrup; in 20 % sugar syrup with 4 % of ascorutin added; in 45 % sugar syrup. The berries were stored at -18 °C. The research results. Studies have shown that the content of sugar in fresh cherry berries was within the range of 10.14−10.96 %. After freezing of cherry berries in 45 % sugar syrup and 20 % sugar syrup with adding 4 % of ascorutin the loss of sugar was the least – 2.26−8.88 % and 3.3−10.16 %, correspondingly. The acid content in the studied cherry berries was 1.67−2.02 %, it was the smallest in Elehantna variety – 1.67 %, and the highest in Pamiat Artemenka – 2.02 %. During the three months of freezing, the acid content decreased by 2.19−11.9 % as compared with fresh berries, and at the end of freezing there was a slight increase in their content by 0.5−3.47 %. The elements of scientific novelty. The berries of Alfa, Pamiat Artemenka, and Shans varieties were distinguished by the most harmonious taste. The least decrease in the sugar-acid index in cherry was observed in berries frozen in 45 % sugar syrup and 20 % sugar syrup with 4 % ascorutin added. Practical significance. In order to preserve a harmonious taste with a high sugar-acid index, the cherry berries must be frozen in 20 % solution of sugar with adding 4 % of ascorutin.